THE ROLE OF INVESTMENTS IN THE DEVELOPMENT OF THE ECONOMY OF UZBEKISTAN - Uralov Jamshid Vokhid ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article discusses the importance of the volume and composition of investment funds attracted to various sectors and industries of the national economy in the socioeconomic development of our country. Emphasis is placed on the central direction of the development strategy of each country, the relevance of shaping a conducive environment for attracting investment funds to enhance the national economy, promote sustainable economic growth, increase the income of the population, and improve living conditions. The article also highlights the significance of formulating scientific proposals and conclusions to increase the volume of investment inflows into the national economy.